Effects of Degossypolized Cottonseed Protein on the Laying Performance, Egg Quality, Blood Indexes, Gossypol Residue, Liver and Uterine Histopathological Changes, and Intestinal Health of Laying Hens - Ru Li; Xingyuan Luo; Shiping Bai; Xuemei Ding; Jianping Wang; Qiufeng Zeng; Yue Xuan; Shanshan Li; Sharina Qi; Xiaojuan Bi; Chao He; Xuanming Chen; et al. (Agriculture)
This experiment aimed to investigate the appropriate level of degossypolized cottonseed protein (DGCP) in the diet of laying hens. A total of 600 49-week-old Lohmann pink laying hens were allocated to five treatments, with six replicates per treatment and 20 birds per replicate. The control group was fed a corn-soybean meal basal diet. Four experimental diets were formulated by replacing 25%, 50%, 75%, and 100% of the soybean meal protein-equivalent capacity with DGCP, where 100% replacement corresponded to the maximum safe inclusion of DGCP. The study period lasted for 8 weeks. The results showed that the feed intake, average egg weight, egg mass, laying rate, and the albumen percentage were significantly reduced in the 100% DGCP group (p < 0.05). Plasma uric acid (UA), total cholesterol (TC), triglyceride (TG), and potassium (K) levels were significantly lower (p < 0.05), and depth of crypt (CD) was significantly higher (p < 0.05) in the 100% DGCP group. The DGCP diet linearly increased the relative abundance of Bacteroidota and Bacteroide and significantly increased the relative abundance of Desulfobacterotas in the cecum contents compared to the control group (p < 0.05). The ACE and Chao1 indices in both the control group and the 100% DGCP group were significantly decreased (p < 0.05). In conclusion, the dietary addition of DGCP can reach up to 114.6 g/kg.